Pemahaman Manajemen Perusahaan tentang Peraturan Perpajakan dan Kepatuhan Wajib Pajak Badan (Studi Kasus di Kota Metro) - . Khomsiyah; Lie Nelly; Haninun HANINUN (Jurnal Akuntansi dan Keuangan, 2010)
This study aims to analyze how an understanding of the companys management and tax laws and how an understanding of the compliance management company corporate taxpayers in Metro City. From the analysis and discussion, it can be concluded that the understanding of the companys management at Metro City on tax laws and compliance with corporate taxpayers is good. This indicates that the company has to understand the obligations and rights as a taxpayer as stated in the taxation legislation.It may be advisable for the company is the management should further deepen the existing section of each item in the tax laws that apply today. As for the tax laws suggested policy makers should not make taxpayers feel difficulty in meeting its obligations as a taxpayer and where to make changes to the tax laws should be communicated to the taxpayer in order to avoid errors in the implementation and fulfillment of the rights of taxpayers.